Evaluation of the Effectiveness of the PANGESTU Application Strategy in Optimizing Online Outpatient Reservations at Hospital X - Kurniawan, Moh Bagus; Sari, Irda (Greenation Publisher & Yayasan Global Research National, 2025)
The digitization of registration services is part of the modernization of healthcare services to speed up administrative processes and improve patient comfort. Hospital X developed the PANGESTU application as an online reservation system for outpatients. Assessing the effectiveness of the PANGESTU application strategy in optimizing the online reservation process and identifying supporting and inhibiting factors in its implementation. The research used a qualitative descriptive approach through observation, interviews with registration officers, security guards, and patients, as well as documentation over a period of six months. The application speeds up the registration process and makes it easier for patients who are familiar with technology. However, obstacles were encountered, such as digital literacy gaps, the illegibility of reservation data, and the lack of formal training for officers. The success rate of an application is highly dependent on the readiness of human resources and the adaptability of the system to user variations. Data integration and digital education are key factors for optimization. The PANGESTU application has successfully created service efficiency, but it is not yet fully inclusive. Technical optimization, improved digital literacy, and active involvement of human resources are necessary to ensure the sustainability of the system.